PENGARUH KKUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL FADIL MOTOR KOTA PEKANBARU - Arif Rahmanda; Syakdanur Nas; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This study aims to determine the influence the quality of service to customer satisfaction at the workshop Fadil Motor Ppekanbaru city. Population in this study were customer of workshop Fadil Motor Pekanbaru as many as 112 customer, and the sample of 53 customer. Measurement of data using the question form and documentation. Analysis of data used is simple linear regression. The result of research based on simple linear regression showed quality of service influence to customer satisfaction at the workshop Fadil Motor Pekanbaru, this can be seen from constant value (a) equal to 45.733 and regression coefficient value (b) equal to 0.479 with regression equation 45.733+0.479. Seen from the calculation of R2 (R Square Change) obtained the value of 0.360. Means that the contribution of quality of service influence on customer satisfaction outcomes of 36,0%..Keyword: Quality of Service, Customer Satisfaction